-3.61=3p+7.7

Simple and best practice solution for -3.61=3p+7.7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3.61=3p+7.7 equation:


Simplifying
-3.61 = 3p + 7.7

Reorder the terms:
-3.61 = 7.7 + 3p

Solving
-3.61 = 7.7 + 3p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-3p' to each side of the equation.
-3.61 + -3p = 7.7 + 3p + -3p

Combine like terms: 3p + -3p = 0
-3.61 + -3p = 7.7 + 0
-3.61 + -3p = 7.7

Add '3.61' to each side of the equation.
-3.61 + 3.61 + -3p = 7.7 + 3.61

Combine like terms: -3.61 + 3.61 = 0.00
0.00 + -3p = 7.7 + 3.61
-3p = 7.7 + 3.61

Combine like terms: 7.7 + 3.61 = 11.31
-3p = 11.31

Divide each side by '-3'.
p = -3.77

Simplifying
p = -3.77

See similar equations:

| F(x)=2ln(x+3) | | -1+8(7-6x)=2x+6 | | 5g-2x=a | | 3L+12=2L+6L+1 | | 4(a+8)+9=12a-9 | | 9=5-4(2x-5) | | 2(k+1)+9=8k-11 | | 10+9(-10-9x)=8-x | | 2(y-5)-7(y)=-15 | | 3(n+10)+11=7n-1 | | 5(b-1)+3(b-1)=4(3-b)+3(4b-2) | | 6(1-2n)=(-3)(n-2) | | x+x+(4*x)+90=180 | | -2-(4-3x)=-7 | | x+x+(4*x)+90=360 | | (-2x-1/3x)×(-9/7x^3y) | | 5x+2.5x+1=55 | | 6(1-2n)=-3(n-2) | | 8x+10x^2-6=17x | | 1-6(2x-3)=-2 | | 5-2(x+2)=9 | | 15x^5+11x^3-14x=0 | | 2x=-32-5(4x-2) | | 5-3(x+2)=9 | | 6(1-2n)=-2(n-2) | | x=y+1-4 | | (9x-8)+(10x+10)= | | Y=x+1-4 | | 4x^2-6x-10-mx-m=0 | | 2.5+10=1.5+17 | | 5x-2(2x+2)=-6 | | 9b-4=1+6(b+11) |

Equations solver categories